Upaya Pemenuhan Kebutuhan Nutrisi Pada Anak Dengan Gastritis - Setyowati, Wulan Agustina, Siti Arifah, S.Kp.,M.Kes, Endang Zulaicha Susilaningsih, S.Kp.,M.Kep (2017)
Background: Gastritic is condition there is an infection in the mucosal side that caused an anuerysm in that mucosal and caused an interuption in the digestive tract. Cause of gastritic is the undiciplinary of mealtime. This is caused the increase of gastric acid by the consumtion of food and drink. Patogen Helicobacter Pylori cause the inflamation of necrocis that caused in the infection therefore there will be an injury of mucosal side followed by the edema, bleeding and also ulkus. The main problem that should be handled children with gastritic is the acomplishment of nutrition requirement, because children with gastritic will feel painful of epigastrium, queasy, puke and anorectia. This is caused by the unfulfillment of nutrition requirement so it cause an increase of gastric acid secretion and will cause a bleeding of side. Based on medical record in health center in January 2016-February 2017 the incidence of gastritis in children as many as 1354 people.Objective: The general objective of this scientific study is to give a nursing direction to increase the children nutrient needs in gastritic. The spesific objective of this study is to analyze the investigation, diagnose, plan, implementation and evaluation. Methods:The method in this case study is deskirptif using nursing care at An.R approach that includes assessment, diagnosis, planning, implementation and evaluation.Finding:After nursing actions during 3x visit to the action form, encourage the family to provide warm meals with small portions but frequently and educate families about the nutritional requirements appropriate for the patient, An.R efforts to fulfill nutritional needs can be met.Conclusion: The way of fulfill An.R nutrient requirement that use a nursing direction is according to the standardization of nursing direction for 3 times visiting, therefore the result is An.R nutrient requirement is fulfilled.